2006
DOI: 10.1111/j.1365-2230.2006.02050.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mizolastine on antigen-induced activation of signalling pathways in murine mast cells

Abstract: PKC-mediated phosphorylation of Akt can be blocked by mizolastine. There may be a PKC-independent pathway effectively activating MAPK pathways in mast cells in response to antigen induction, which cannot be affected by mizolastine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…In a previous report from this laboratory, impaired PI3K/Akt activation with increased TNF‐α was shown to reduce NF‐κB activation (26), which has been shown to be involved in the increase of apoptosis in keratinocytes in the depigmented compared to the normally pigmented epidermis in vitiligo (25). Because histamine has been shown to increase PI3K and Akt activation (36,37), it was expected that the histamine could increase the survival of vitiliginous keratinocytes, with an in vitro model that was prepared with cultured normal human keratinocytes in the presence of TNF‐α and wortmannin, a PI3K inhibitor. In fact, histamine, particularly the H2 receptor agonist, reduced the loss of vitiliginous keratinocytes (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous report from this laboratory, impaired PI3K/Akt activation with increased TNF‐α was shown to reduce NF‐κB activation (26), which has been shown to be involved in the increase of apoptosis in keratinocytes in the depigmented compared to the normally pigmented epidermis in vitiligo (25). Because histamine has been shown to increase PI3K and Akt activation (36,37), it was expected that the histamine could increase the survival of vitiliginous keratinocytes, with an in vitro model that was prepared with cultured normal human keratinocytes in the presence of TNF‐α and wortmannin, a PI3K inhibitor. In fact, histamine, particularly the H2 receptor agonist, reduced the loss of vitiliginous keratinocytes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…(*P < 0.05). been shown to increase PI3K and Akt activation (36,37), it was expected that the histamine could increase the survival of vitiliginous keratinocytes, with an in vitro model that was prepared with cultured normal human keratinocytes in the presence of TNF-a and wortmannin, a PI3K inhibitor. In fact, histamine, particularly the H2 receptor agonist, reduced the loss of vitiliginous keratinocytes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although the receptors and signaling pathway of these antihistamines in vertebrates such as humans are already known, the detailed mechanisms in marine invertebrates remain unknown. As mizolastine affects both the generation and release process of many cytokines in cells, targeting signaling pathways, inhibiting inflammation-induced activity, and exhibiting anti-angiogenesis properties (Carayol et al 2002;Xia et al 2005Xia et al , 2006, a promising research direction should involve linking its substantial and reversible anti-settlement activity with its known biochemical functions, and further, possibly clarifying the biochemical regulation of biofouling.…”
mentioning
confidence: 99%
“…In contrast, most studies have suggested that phosphoinositide 3-kinase, and not p38 MAPK, is responsible for activation of Akt isoforms. Other data suggest that MAPK activation may inhibit Akt activation (20 -22), particularly in intestinal epithelia, or that Akt activation can lead to p38 MAPK activation (23,24). Thus, while existing data suggest that a relationship between p38 MAPK and Akt exists in many systems, the intermediates involved in this process, and even the direction of the effect, are controversial.…”
mentioning
confidence: 99%